1996
DOI: 10.1051/parasite/1996033209
|View full text |Cite
|
Sign up to set email alerts
|

Local immune response to experimentalFasciola hepaticainfection in sheep

Abstract: Summary :Macrophages, eosinophils, neutrophils and lymphocyte subpopulations (OvCD5+, OvCD4+, OvCD8+, OvWC1+ and lg + ) were identified in sections of hepatic tissue and hepatic lymph nodes from sheep experimentaly infected with F. hepatica and necropsied 14, 28, 42 or 56 days post infection. The migratory tunnels produced by juvenile flukes appeared as focal areas of necrosis surrounded by infiltrating inflammatory cells, particularly numerous macrophages, eosinophils and OvCD4 + lymphocytes. In addition, B l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
13
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 10 publications
10
13
0
2
Order By: Relevance
“…The same IgM responses were noted in other hosts such as sheep (Chauvin et al, 1996) and to other trematodes such as Schistosoma mansoni (Khalif et al, 1985). Thus IgM may act as a blocking isotype during fasciolasis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The same IgM responses were noted in other hosts such as sheep (Chauvin et al, 1996) and to other trematodes such as Schistosoma mansoni (Khalif et al, 1985). Thus IgM may act as a blocking isotype during fasciolasis.…”
Section: Discussionsupporting
confidence: 60%
“…The local immune response in the area surrounding young flukes during migration through the liver which may play a role in resistance mechanisms has been explored less. Chauvin et al, (1996) showed that the migratory tunnels produced by juvenile flukes in sheep liver appeared as focal areas of necrosis surrounded by infiltrating inflammatory cells, in particular numerous macrophages, eosinophils and OvCD4 + lymphocytes. Moreover, during chronic infection and re-infection in sheep, the number of CD8 + lymphocytes became greater than that of CD4 + (Meeusen et al, 1995).…”
mentioning
confidence: 99%
“…Resistance to reinfection and host response to F. hepatica vary greatly between species [12]. Several studies have investigated immune response to F. hepatica in sheep [4,5,16]. These studies reported that sheep do not develop resistance to reinfection.…”
Section: Introductionmentioning
confidence: 99%
“…Local and systemic immune responses have been studied in sheep infected and reinfected with F. hepatica [4,5,16]. More recently, the effects of infection and treatment on subsequent challenge have been studied in cattle [13].…”
Section: Introductionmentioning
confidence: 99%
“…The release of cytokines by lymphocytes is triggered by antigen recognition, which in turn initiates and regulates cell-to-cell communication. Granuloma formation, Ig isotype and the massive eosinophilia observed after 14 days of infection with F. hepatica indicate an oriented Th2 immune response [4,17,26]. However, before day 14 postinfection (pi), such data are unavailable and it is difficult to analyse the immune response by these means.…”
Section: Introductionmentioning
confidence: 99%